Cancel Culture: A Case Study on the Experiences of Called-out Person in Social Media - Palomares, Mary Ann; Dumlao, Reinyer; Cabacungan, Lovely Joy; Acera, Anniekins; Ancheta, Wendy Mae; Gelacio, Rejean; Martin, Benjie; Abordo, Christian; Aglugub, Rovalyn Joy; Balmaceda, Diana (International Journal of Arts, Sciences and Education, 2022)
The study aimed to investigate people’s experiences called out in social media. Twenty victims from both international and local who experienced called out were used as the sampling frame in this study. The study used a case analysis method by gathering data from the web and interviews. It was found out that the victims had factors involved, subsequent effects, and realization. The victims took their actions personally, which resulted in some apologizing for their actions.